Persistent elevation of blood pressure by ambient coarse particulate matter after recovery from pulmonary inflammation in mice. Issue 7 (27th March 2019) - Ho, Chia‐Chi; Tsai, Ming‐Hsien; Chen, Yu‐Cheng; Kuo, Cheng‐Chin; Lin, Pinpin
Abstract: Exposure to ambient particulate matter (PM) is associated with hypertension and cardiovascular diseases. Recently, we reported that exposure to fine and coarse PM caused pulmonary inflammation and pulmonary small arterial remodeling in mice, and osteopontin (OPN) level was elevated following PM exposure. However, in the present study, cotreatment with 5‐methoxytryptophan for 4 weeks partially reduced coarse PM‐induced pulmonary inflammation without reducing pulmonary OPN secretion or recovery from pulmonary arterial remodeling in mice. Persistent vascular dysfunction may lead to vascular remodeling. Therefore, we further compared the relationship between coarse PM‐induced inflammation and vascular dysfunction by exposing mice to PM before and after cessation of PM exposure. Oropharyngeal aspiration of PM for 8 weeks induced pulmonary inflammation and pulmonary small artery remodeling in mice, as well as increased serum C‐reactive protein and OPN concentrations and systolic blood pressure (SBP). After the cessation of PM exposure for another 8 weeks, lung inflammation had recovered and vascular remodeling had partially recovered. Elevation of OPN, metalloproteinases (MMPs), and cytokines in bronchioalveolar lavage were significantly reduced. However, PM‐induced systemic responses did not recover after the cessation of PM exposure. Notably, not only serum OPN and SBP remained significantly elevated; also, serum endothelin‐1, MMP‐9, and keratinocyte‐derived chemokine concentrations were significantly increased after cessation of PM exposure for another 8 weeks. These data suggested that systemic inflammation and systemic vascular dysfunction might be important in PM‐induced elevation of SBP. Furthermore, SBP elevation was persistent after cessation of PM exposure for 8 weeks.